Efektivitas Dinas Pemberdayaan Perempuan dan Perlindungan Anak (DPPPA) Kota Semarang dalam Penanganan kasus kekerasan terhadap Anak Di Kota Semarang - Ajeng Resi Krisdyawati; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Every child has the right to survival, development and growth and has the right to protection from violence and discrimination as mandated in Article 28B of the 1945 Constitution of the Republic of Indonesia. Protection of women and children aims to prevent acts of violence against women and children including human traffict, This study aims to describe and analyze the effectiveness of the Office of Women's Empowerment and the Protection of the City of Semarang in handling cases of violence against children in the city of Semarang and describe what the supporting and inhibiting factors of handling cases of violence against children that affect. The results of this study indicate that the effectiveness of the organization in the Office of Women's Empowerment and Protection of the City of Semarang in handling cases of violence against children has not been as expected. In the source approach, it can be seen that the supporting facilities are available enough to be utilized by the community. Then in the process approach, communication is created dynamically and always applies a culture of deliberation. But it still has obstacles in environmental characteristics, namely the limited number of employees. Researchers suggest optimizing the role of employee orientation in providing services must always be oriented to the private sector so that employee attitudes can be more flexible adjusting the background of the people who come and improve prevention programs for cases of violence against children.